Impact of annealing on the formation and mitigation of carrier-induced defects in multi-crystalline silicon. (September 2017) - Fung, Tsun Hang; Chan, Catherine E.; Hallam, Brett J.; Payne, David N.R.; Abbott, Malcolm D.; Wenham, Stuart R.
Abstract: Carrier-induced degradation (CID) of multi-crystalline silicon (mc-Si) wafers is a major problem currently affecting the photovoltaic industry. A large number of studies investigating this phenomenon have provided important clues regarding the identification of the defect, however, as of yet, none have isolated a specific cause. In this work, we provide further insight into the kinetics of CID in mc-Si by presenting a detailed study of the impact of dark annealing on the formation and subsequent mitigation of the carrier-induced defect. Previous work has shown that such anneals can modulate the kinetics of the defect. Here, we extend that work and demonstrate that dark annealing can result in accelerated defect formation and extended degradation throughout a subsequent light soaking cycle, irrespective to when the dark annealing was applied. It is suggested that dark annealing could release extra defect precursors into mc-Si, which then become recombination active upon illumination. Therefore, the subsequent degradation after dark annealing might not necessary involve a reverse reaction. Through multiple dark anneal and light soak cycles, the extent of degradation in each cycle continues to reduce. A direct reverse reaction (de-stabilisation) alone does not explain this observation. We suggest that this effect could be explained by the presence of a reservoir of defect precursors, which are gradually depleted throughout the dark annealing processes. Finally, it is demonstrated that dark annealing alone could potentially cause a similar degradation to illumination at elevated temperature.